Biosynthesis and characterization of Iron oxide nanoparticles by Mentha Pulegium .L leaf extract - Bouafia, Abderrhmane; Laouini Salah Eddine (University Of Eloued جامعة الوادي, 2020)
In this study, green synthesis of iron oxide nanoparticles was successfully prepared from Mentha Pulegium L leaves extract. The effect of different ferric chloride concentrations on the nanoparticles' iron oxide formation was studied. The obtained nanoparticles were characterized by UV-Vis, FT-IR, XRD, SEM and EDAX techniques are used for this purpose. UV-Vis spectra showed maximum absorption at range 275-301 nm related to the iron oxide. FTIR spectra exhibit a two weak peak at 510 and 594 cm-1 attributed to iron oxide NPs vibration, confirming the formation nanoparticles XRD confirmed the crystalline nature of Fe3O4 and α-Fe2O3 NPs with average size ranged in 22-34 nm.SEM showed that the green synthesizing Iron oxide nanoparticles having in general as cubical shape. As a result, the use of Mentha Pulegium L leaves extract offers its ease, fast, low cost and friendly to the environment compared to other methods.
Intervention
Keywords: Iron Oxide; Mentha Pulegium L; Ferric Chloride; Green Synthesis; XRD